The accuracy of fetal pulse oximetry in the second stage of labour - Johnson, N; Johnson, V A; Bannister, J; Lilford, R J (Journal of perinatal medicine, 1991)
The aim of this study is to assess the accuracy of fetal monitoring with pulse oximetry at delivery. The pulse oximetry reading from the fetus at delivery was compared to fetal condition at birth. There is poor correlation between fetal scalp oximetry readings at delivery and fetal condition (Apgar scores), umbilical venous or arterial blood gas analysis or pH. Although there are good theoretical reasons why the correlation should not be perfect, the wide deviation from expected values suggest that readings taken during delivery are particularly prone to errors. Examination of the unprocessed photodetector signal during the second stage of labour reveals considerable movement interference. The signal may also be affected by congestion and transmitted venous pulsation in the scalp as the head crowns. The current generation of reflectance pulse oximeters can predict fetal hypoxemia during labour but a single reading during delivery is subject to too much movement interference to produce useful data.